Upper limb kinematics during the topspin double-handed backhand stroke in tennis - Busuttil, N.; Reid, M.; Connolly, M.; Dascombe, B.; Middleton, K. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to compare non-dominant wrist kinematics during tennis double-handed backhand strokes in players using either an eastern or continental grip position. Trajectory data for two grips (eastern & continental) and depths (deep & short) were captured for sixteen sub-elite right-handed tennis players using a 12-camera Vicon motion capture system (250 Hz). The eastern grip demonstrated significantly faster horizontal racket head velocities compared to the continental grip. However, no differences were observed in accuracy or spin rate between grips (p > 0.05). In the non-dominant upper limb for the continental condition, elbow flexion was smaller while wrist extension was larger throughout the swing. Collectively, these data suggest that the continental grip may place the wrist in a position that is more vulnerable to overuse injury.